2009
DOI: 10.1098/rspb.2008.1811
|View full text |Cite
|
Sign up to set email alerts
|

How chimpanzees look at pictures: a comparative eye-tracking study

Abstract: Surprisingly little is known about the eye movements of chimpanzees, despite the potential contribution of such knowledge to comparative cognition studies. Here, we present the first examination of eye tracking in chimpanzees. We recorded the eye movements of chimpanzees as they viewed naturalistic pictures containing a full-body image of a chimpanzee, a human or another mammal; results were compared with those from humans. We found a striking similarity in viewing patterns between the two species. Both chimpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
173
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(200 citation statements)
references
References 22 publications
21
173
4
Order By: Relevance
“…But species differences in viewing faces may be more apparent in tasks using dynamic objectdirected actions of others than in tasks that require observers to merely look at still images. Second, although our data on species difference in the grand average of fixation durations are comparable to those of a previous studies (200-300 ms in chimpanzees and 200-700 ms in human adults) 22,27 , our results showed that the fixation durations of chimpanzees differ according to the target of fixations. When fixations to faces were considered, the average fixation duration was shorter in chimpanzees than in humans (for example, 229 ms in chimpanzees and 672 ms in human adults in Experiment 1), but the duration of fixation to the object did not differ between chimpanzees and humans (for example, 490 ms in chimpanzees and 579 ms in human adults in Experiment 1).…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…But species differences in viewing faces may be more apparent in tasks using dynamic objectdirected actions of others than in tasks that require observers to merely look at still images. Second, although our data on species difference in the grand average of fixation durations are comparable to those of a previous studies (200-300 ms in chimpanzees and 200-700 ms in human adults) 22,27 , our results showed that the fixation durations of chimpanzees differ according to the target of fixations. When fixations to faces were considered, the average fixation duration was shorter in chimpanzees than in humans (for example, 229 ms in chimpanzees and 672 ms in human adults in Experiment 1), but the duration of fixation to the object did not differ between chimpanzees and humans (for example, 490 ms in chimpanzees and 579 ms in human adults in Experiment 1).…”
Section: Discussionsupporting
confidence: 50%
“…The present results offer new species differences; first, the degree of species difference gauged by the proportion of fixation to faces is larger in our study than the previous study in which participants looked at still photographs containing the whole body of human and non-human animals, although strict comparison is not possible because of methodological differences 22 . But species differences in viewing faces may be more apparent in tasks using dynamic objectdirected actions of others than in tasks that require observers to merely look at still images.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations